Medical escape games: experimenting with a new teaching method - Larouche, Pauline; Sweeney, Kevin; Lajeunesse, Judith (Canadian Medical Education Journal, 2023)
Implication Statement With escape games gaining in popularity, we decided to adapt the concept of an existing medical escape game to the needs of our family medicine residents, by simulating clinical situations and creating puzzles with medical content. This activity was a fun way to integrate theoretical learning while developing a number of CanMEDS roles. Overall, the residents were very satisfied with the topics chosen and the interactive aspect of the experience. This escape game requires few resources, is adaptable to different environments and can be adjusted according to students' needs.